Analysis of the Therapeutic Effect and Prognostic Factors of 126 Patients With Hypertensive Cerebral Hemorrhage Treated by Soft-Channel Minimally Invasive Puncture and Drainage - Wu, Jiaxun; Zhang, Sunfu (Frontiers in Surgery, 2022)
Surgery is the main method for clinical treatment of hypertensive cerebral hemorrhage. Traditional craniotomy faces the disadvantages of long operation time, easy to cause secondary injury to patients during the operation and prone to infection after operation, which is not conducive to the rehabilitation of patients. At present, it is urgent to find a surgical scheme which can clear hematoma in time, protect brain tissue and effectively reduce surgical trauma in clinic.